Phylogeny analysis of Colutea L. (Fabaceae) from Iran based on ITS sequence data - LEILA MIRZAEI; IRAJ MEHREGAN; TAHER NEJADSATARI; MOSTAFA ASSADI (Society for Indonesian Biodiversity, 2015)
Mirzaei L, Mehregan I, Nejadsatari T, Assadi M. 2015. Phylogeny analysis of Colutea L. (Fabaceae) from Iran based on ITS sequence data. Biodiversitas 16: 168-172. This study was carried out on the species of Colutea L. that growing in Iran. Some of thesespecies are native to Iran. Internal transcribed spacer (ITS) sequences were obtained from 12 samples representing seven species ofColutea recognized by recent taxonomic treatments from Iran and we used 20 ITS sequences from GenBank to test the phylogeny ofColutea. Phylogenetic analyses were conducted using Bayesian inference and maximum likelihood methods. Our results of cladisticanalysis of phylogenetic relationships among Coluteae tribes showed its monophyletic origin and Astragaleae was its sister group. Inaddition, C. cilicica was a sister group to C. gifana whose separated of other Colutea genus from Iran. Bayesian inference and maximumparsimony analyses confirmed the monophyly of three sections of Colutea in Iran. Our results showed that further investigationincluding application of larger number of markers and involving all the Iranian Colutea species will be more effective in estimation therelationships of the genus.